JUDICAL ANALYSIS OF THE ECONOMIC RIGHTS IN THE LAKE TOBA NATIONAL STRATEGIC TOURISM AREA IN OF FROM PRESIDENTIAL REGULATION NO.81 OF 2014 CONCERNING SPATIAL PLAN FOR THE LAKE TOBA AREA AND LAW NO.11 OF 2005 CONCERNING THE INTERNATIONAL COVENANT ON ECONOMIC,SOCIAL AND CULTURAL RIGHTS - Siregar, Kristian (Transnational Business Law Journal, 2022)
The ideals of the Indonesian nation as stated in the Preamble of the 1945 Constitution require that the general welfare be realized. To realize these ideals, human rights, in this case economic rights, are one of the indicators used as a basis for implementing a program, decision or regulation. Economic rights are generally described as rights related to the conditions of existence and welfare in terms of owning and utilizing something for their survival. The status of economic rights in the 1945 Constitution and Law No.11 of 2005 places economic rights as rights that must be protected, respected and fulfilled by the state. One of them is in the Tourism sector. Economic Rights play an important role in the creation of a prosperous community life in the area that is the object of Tourism. However, economic rights in reality are often ignored by the government as a consideration in loading policies and regulations, so that in its implementation it creates conflict between the community and the government. The purpose of this research is to find out how the protection and fulfillment of economic rights in the tourism development sector correlates with the level of community welfare